(untitled) (Gestión y Gerencia, 2023)
Knowledge management as a necessary strategy to manage knowledge, in order to make the organization more efficient and effective every day when making timely decisions and at the same time maintaining a sustainable competitive advantage is the objective of this research. Every day institutions require new and different tools, strategies, systems, innovative processes that allow them to face the constant changes and be able to survive in a convulsed, complex and competitive world. In the era of artificial intelligence (AI) knowledge is analyzed as an indispensable tool in the management of organizations. For the methodology, a questionnaire designed for this purpose is used. Knowledge management becomes a useful and easy-to-reach strategy in terms of cost and time, it must be executed in an orderly, practical and effective manner with all the knowledge of each one of the institutions’ collaborators, in order to make them useful for their development and growth. In conclusion, knowledge management is a potential strategy for management since its application takes advantage of the experiences of its workers to improve the efficiency and effectiveness of its operations, in addition to facilitating the detection of any problem within the organization.